Pengaruh Terapi Musik Klasik Terhadap Penurunan Tingkat Nyeri Pada Pasien Post-Operasi Di Lantai 4 Paviliun Eri Soedewo RSPAD Gatot Soebroto Jakarta: The Effect of Classical Music Therapy on Reducing Pain Levels in Post-operative Patients on the 4th Floor of the Eri Soedewo Pavilion, Gatot Soebroto Army Hospital, Jakarta - Turyono, Turyono (Indonesian Scholar Journal of Nursing and Midwifery Science (ISJNMS), 2024)
Introduction: Pain is an unpleasant feeling subjective sensory and emotional experience related to actual or potential tissue damage. The experience of pain is different for each individual, the experience of pain involves physical, emotional and cognitive components the pain felt can interfere with personal relationships. Post-surgical pain is the most frequently complained of by patients after surgery and remains a major clinical problem if it is not treated. Music therapy is a distraction technique used to divert unpleasant sensations for a person for example pain in post-operative patients. The aim of this research is to determine the effect of classical music therapy on reducing pain levels in post-operative patients.  Methods: In this research, researchers used quantitative research the research method was Pre-Experimental Design. The population in this research were all post-operative patients who experienced pain on the 4th floor of the Eri Soedewo Pavilion Gatot Soebroto Army Hospital, Jakarta. The sampling technique in this research used a purposive sampling technique. So the sample in this study consisted of 30 respondents. The data collection technique used in this research is the Numeric Rating Scale (NRS). This research uses the Wicoxon Two Related Sample Test Statistical Test. Results: The results of pain scale research before classical music therapy was given to post-operative patients showed that the majority of patients experienced moderate pain 18 people (54%). The pain scale after classical music therapy was carried out on post-operative patients showed that the majority of patients experienced moderate pain, 14 people (47%). The results of statistical tests using Wilcoxon showed a calculated Z value of -4,54 with an Asym Sig value of 0,000 (p < 0,05). Discussion: The majority of the pain scale before classical music therapy was carried out in post-operative patients on the 4th floor of the Eri Soedewo Pavilion, Gatot Soebroto Army Hospital was moderate pain. The majority of pain scales after classical music therapy in post-operative patients on the 4th floor of the Eri Soedewo Pavilion Gatot Soebroto Army Hospital are moderate pain. There is an effect of classical music therapy on reducing pain levels in post-operative patients on the 4th floor of the Eri Soedewo Pavilion Gatot Soebroto Army Hospital Jakarta.